Transitional Justice, Victims and Human Rights in the Light of International Law and the Inter-American System of Human Rights - Quispe Remón, Florabel (The Age of Human Rights Journal, 2021)
The article begins by analyzing the origin and evolution of the concept "transitional justice", determining its characteristics, the context in which it was born and developed, as well as the role of the State in this process. Then it focuses attention on analyzing the development of this figure in the jurisprudence of the Inter-American Human Rights System, through the work that the Inter-American Court has been carrying out since its operation, interpreting in a broad way and always pro homini, the American Convention of Human Rights. Throughout its years of operation, it has ruled on the State’s obligation to protect and guarantee human rights and to carry out the pertinent investigations in the event of their violation; as well as the recognition of the status of victims to the victims’ families and their pronouncement of the right to the truth, not as an autonomous human right, but rather as a right of the victims and their next of kin. Undoubtedly, these are aspects that have gone beyond the American Convention.